Comparing Query Logs and Pseudo-Relevance Feedback for Web-Search Query Refinement - White, Ryen W.; Clarke, C.L.A.; Cucerzan, Silviu (Proceedings of SIGIR 2007, 2007)
Query logs and pseudo-relevance feedback (PRF) offer ways in which terms to refine Web searchers’ queries can be selected, offered to searchers, and used to improve search effectiveness. In this poster we present a study of these techniques that aims to characterize the degree of similarity between them across a set of test queries, and the same set broken out by query type. The results suggest that: (i) similarity increases with the amount of evidence provided to the PRF algorithm, (ii) similarity is higher when titles/snippets are used for PRF than full-text, and (iii) similarity is higher for navigational than informational queries. The findings have implications for the combined usage of query logs and PRF in generating query refinement alternatives.